Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 11 - Additional Topics - 11.3 - Fractional Exponents - Problem Set 11.3: 49

Answer

49

Work Step by Step

We will use the rule $\frac{a^{m}}{a^{n}}=a^{m-n}$ in the simplification of the expression: $\frac{7^{\frac{4}{3}}}{7^{-\frac{2}{3}}}=7^{\frac{4}{3}-(-\frac{2}{3})}=7^{\frac{4}{3}+\frac{2}{3}}=7^{\frac{4+2}{3}}=7^{\frac{6}{3}}=7^{2}=49$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.